2018
DOI: 10.1016/j.jss.2018.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics contrasted to thrombelastography: perplexities in defining hypercoagulability

Abstract: Background: Elevated clot strength (maximum amplitude [MA]) measured by thrombelastography (TEG) is associated with thrombotic complications. However, it remains unclear how MA translates to thrombotic risks, as this measurement is independent of time, blood flow, and clot degradation. We hypothesize that under flow conditions, increased clot strength correlates to time-dependent measurements of coagulation and resistance to fibrinolysis. Materials and methods: Surgical patients at high risk of thrombotic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…We also believe that much more attention needs to be given to assessment of hypercoagulability (compared with bleeding) during pregnancy, particularly in placenta‐mediated complications with complex coagulopathies such as preeclampsia, gestational diabetes, or recurrent miscarriage. Indeed, extensive evidence for the effectiveness of TEG/ROTEM in identifying hypercoagulability has been demonstrated in various clinical conditions, including cancer and preeclampsia . TEG/ROTEM applications in hypercoagulability and thrombosis in pregnancy remain to be expanded.…”
Section: Discussionmentioning
confidence: 99%
“…We also believe that much more attention needs to be given to assessment of hypercoagulability (compared with bleeding) during pregnancy, particularly in placenta‐mediated complications with complex coagulopathies such as preeclampsia, gestational diabetes, or recurrent miscarriage. Indeed, extensive evidence for the effectiveness of TEG/ROTEM in identifying hypercoagulability has been demonstrated in various clinical conditions, including cancer and preeclampsia . TEG/ROTEM applications in hypercoagulability and thrombosis in pregnancy remain to be expanded.…”
Section: Discussionmentioning
confidence: 99%
“…MA was used to assess the intensity of blood clots. Due to platelet count and function, MA value was associated with platelet action, and elevated MA value suggested that blood was hypercoagulable [6]. Studies have shown that the MA value and the probability of thrombosis have higher sensitivity and specificity, the MA value increases, and the probability of thrombosis increases significantly [7].…”
Section: Mamentioning
confidence: 99%
“…This assay has the advantage of operating at physiological shear rates and in an open system, but generates only a single clot per chip, has shown a poor correlation with direct oral anti-coagulant (DOAC) doses, and has poor agreement with the more established thromboelastographic methods. 23,24 This study used validated flow experiments and reagents from PDMS microfluidic techniques and deployed an injection molded chip to create a versatile technology for medical professionals at the bedside. [1][2][3]7,9,19 A POC microfluidic device needs to (1) utilize small volumes (<1 ml) of whole blood, (2) have a scalable production method, (3) be simple to prime and operate by non-expert users, (4) retain uniform flow behavior across all test conditions, (5) be storage stable in a prepared state, and (6) have a total experimental footprint suitable for benchtop use.…”
Section: Introductionmentioning
confidence: 99%